Vulneraciòn del debido proceso por la reprogramaciòn injustificada de las audiencias en los procesos laborales en Trujillo - Chàvez Gamboa, Brenda Miluska (2019)
The purpose of this research is to demonstrate that the unjustified reprogramming of audiences distorts the labor process that has been designed based on the principles of speed, concentration and procedural economy; thus violating the constitutional guarantee of Due Process. In the New Procedural Law of Labor, three cases have been regulated that originate the reprogramming of the hearings: the inconsistency of the parties, the incorporation of the ex officio evidence and the evidentiary sanitation as a manifestation of the leading role of the judge; Assumptions that, after carrying out the present investigation, have been verified are being distorted by the Operators of justice. Thus, with regard to the inconsistency of the parties, the labor procedural rule regulates the opportunity to request the reprogramming of the hearing not carried out; however, the trial lawyers conceive their non-attendance at the hearings and later reprogramming them as part of their right to Effective Jurisdictional Guardianship, and request that a new date be set for the performance of this procedural act without indicating, let alone accrediting the reason that caused his non-attendance; lacking in this their duties of collaboration and at the same time manifesting a reckless behavior and bad faith that can be sanctioned, because with this act not only originates the unnecessary delay of the process in which this diligence is not carried out, but also of the other judicial processes in process whose hearings hope to occupy a space in the overloaded judicial agenda. This situation is aggravated by the mismanagement of the process carried out by the labor judge who does not correctly assume its leading role in the development of the same, ceasing to sanction the unjustified inconsistency of the parties to the scheduled audiences, as well as making an incorrect incorporation of the ex officio proof, and finally, failing to timely carry out the evidentiary sanitation in order to avoid future suspensions of the hearings. Delimited the problem, it is concluded that the Operators of justice, especially the judge, are the main architects of the reform of the labor process, which requires their participation according to the guidelines established by law, because only then will a due process be achieved that gives rise to an effective guardianship; and, based on this, the university community is recommended to continue with the investigation of the procedural act of the audience, as it is the neuralgic aspect of an oral process such as the Peruvian labor process.